2009
DOI: 10.1101/gad.1836009
|View full text |Cite|
|
Sign up to set email alerts
|

Ly6d marks the earliest stage of B-cell specification and identifies the branchpoint between B-cell and T-cell development

Abstract: Common lymphoid progenitors (CLPs) clonally produce both B-and T-cell lineages, but have little myeloid potential in vivo. However, some studies claim that the upstream lymphoid-primed multipotent progenitor (LMPP) is the thymic seeding population, and suggest that CLPs are primarily B-cell-restricted. To identify surface proteins that distinguish functional CLPs from B-cell progenitors, we used a new computational method of Mining Developmentally Regulated Genes (MiDReG). We identified Ly6d, which divides CLP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
345
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 271 publications
(378 citation statements)
references
References 29 publications
25
345
0
Order By: Relevance
“…These factors set up a self-promoting feed-forward loop that establishes B-cell identity while eliminating differentiation into other affiliated cell lineages Rolink et al 1999;Pongubala et al 2008;Lin et al 2010;Treiber et al 2010;Nechanitzky et al 2013;Boller et al 2016). FOXO1 and EBF1 support each other's expression, while EBF1 also induces PAX5 that further augments EBF1 (Roessler et al 2007;Decker et al 2009;Inlay et al 2009;Mansson et al 2012).…”
Section: Lymphoid Lineage Commitment: An Ikaros Time Outmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors set up a self-promoting feed-forward loop that establishes B-cell identity while eliminating differentiation into other affiliated cell lineages Rolink et al 1999;Pongubala et al 2008;Lin et al 2010;Treiber et al 2010;Nechanitzky et al 2013;Boller et al 2016). FOXO1 and EBF1 support each other's expression, while EBF1 also induces PAX5 that further augments EBF1 (Roessler et al 2007;Decker et al 2009;Inlay et al 2009;Mansson et al 2012).…”
Section: Lymphoid Lineage Commitment: An Ikaros Time Outmentioning
confidence: 99%
“…In a parallel process in the bone marrow, a subset of CLPs (also known as B lineage-restricted progenitors [BLPs]) under the influence of IL-7R signaling, E2A, and HEB induce expression of FOXO1 and EBF1 (Inlay et al 2009;Lin et al 2010;Welinder et al 2011). These factors set up a self-promoting feed-forward loop that establishes B-cell identity while eliminating differentiation into other affiliated cell lineages Rolink et al 1999;Pongubala et al 2008;Lin et al 2010;Treiber et al 2010;Nechanitzky et al 2013;Boller et al 2016).…”
Section: Lymphoid Lineage Commitment: An Ikaros Time Outmentioning
confidence: 99%
“…The CLP compartment is heterogeneous, consisting of cells with different defined lineage potentials, as well as cells already committed to the B-cell fate. The CLP compartment can be segregated into two distinct populations based on the expression of the cell surface marker LY6D (4,5). During the last two decades, a subset of transcriptional regulators have been identified that specify and promote B-cell fate.…”
mentioning
confidence: 99%
“…for mature hematopoietic lineages. CD27 is expressed on HSCs and MPPs, and together with the red blood cell marker Ter119, can be used in place of Lin 14, 24, 25. Because this population (CD27+ Ter119– Kit+ Sca‐1+) is identical to the original KLS population (Lin‐ Kit+ Sca‐1+), we keep the nickname “KLS” for simplicity.…”
Section: Resultsmentioning
confidence: 99%